Measuring eating motives in older adults with and without functional impairments with The Eating Motivation Survey (TEMS). (1st June 2019) - Rempe, Hanna M.; Sproesser, Gudrun; Gingrich, Anne; Spiegel, Alexandra; Skurk, Thomas; Brandl, Beate; Hauner, Hans; Renner, Britta; Volkert, Dorothee; Sieber, Cornel C.; Freiberger, Ellen; Kiesswetter, Eva
Abstract: Gaining a better understanding which motives play a role in daily eating is crucial in order to develop personalized interventions promoting adequate diet. The Eating Motivation Survey (TEMS) is a comprehensive tool to assess manifold reasons for eating but has not been specifically applied in an older sample including very old persons and persons differing in functional status. Therefore, the first step of the study was to investigate whether the basic motives of TEMS are consistent in an older sample and comparable across older adults with and without functional impairments. Second, the study aimed at describing which motives underlie eating behavior in older age most often as well as to analyze the relationship between eating motives and functional status. 376 community-dwelling older persons aged 70 years and older filled in the brief survey version (15 motives à 3 items) of TEMS. The sample comprises 149 unimpaired and 227 impaired participants in terms of physical function. Confirmatory factor analysis yielded good model fit with RMSEA 0.036 and SRMR 0.048. Furthermore, multi-group analysis revealed a generally invariant factor structure across participants with and without functional impairments. Liking was rated to underlie eating behavior most often, followed by Health and Natural Concerns. Considering gender, age and BMI, significant associations between functional status and the motive Sociability emerged. Since the results suggest that the fifteen basic eating motives are generalizable in older age and across different functional states, TEMS might be a valuable tool in nutrition-related health promotion to developing individualized approaches considering health aspects as well as hedonistic factors.